The effect of Nd : YAG laser beam on aluminium surface coated with Fe-SiC - Thahe, Asad A. (2013)
Laser ablation on aluminium base coated with Fe-SiC is reported. A qswitched Nd:YAG laser was employed as a source of energy. The fundamental wavelength of the laser beam is 1064 nm with output energy of 100 mJ and pulse duration of 10 ns. The laser was conducted in repetitive mode with frequency rate of 1 Hz. The laser was focused to induce plasma formation. Pure aluminium plate was employed as a substrate for laser ablation. Metal element iron (Fe) and ceramic material silicon carbide SiC were selected to be as laser ablation elements. Both of the elements were mixed together in a ratio of 2:1 (Fe:SiC). Two step deposition techniques were chosen in this work to predeposite the aluminium substrate. The substrate was painted with cohesive material gum before powder spray coating on it. The predeposit aluminium was then exposed with focused laser at various numbers of pulses (1 – 13 pulses). The created material was examined via scanning electron microscope (SEM), x-ray diffraction (XRD) machine and microhardness Vicker HV machine. The microstructure of the created surface was examined via SEM and the results showed the effect of homogenized resolidified area. The plasma temperature is much higher than the melting point of the laser ablation material Fe and SiC thus immediately after plasma interaction with coating materials most of them are melted. The fluid flow over the surface and resolidified during cooling. However the melting temperature between Fe, SiC and Al are different, this allows new composite formation during quenching. The formation of such new composite is identified through XRD analysis. Inherently, several new composites are revealed such as Al- Fe-Si, SiAl and Fe-Si. The formation of such new composite is also indicators for the increment in the strength of the created materials. This is validated by measuring the hardness of the created material. Apparently, the hardness of the modified surface is confirmed to be two times greater than the original substrate.